Perkembangan Arsitektur Isam: Mengenal Bentuk Arsitektur Islam di Nusantara - Hidayatulloh, Haris (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2020)
Conceptually this paper aims to know architecture in the Islamic tradition and the history of the development of Islamic architecture from time to time, to know the main characteristics of Islamic architecture, and to find out the form of Islamic architecture in the archipelago. Using the literature study method, this article produces findings, (1) the sense of admiration of Muslims for the beauty and aesthetics of Islamic architecture is inseparable from the submission and surrender of Muslims to the greatness and majesty of the Creator who is believed to have all the beauty (2) Islamic architecture does not have form one and uniform, but different. (3) factors that influence the form of Islamic architecture include geographical factors, local culture, and traditions, building functions.